Republic of Lithuania : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Lithuania showed strong economic growth with low inflation owing to its sound economic policies. Executive Directors commended this development, and appreciated Lithuania for signing the European Union Accession Treaty. They encouraged the authorities to maintain macroeconomic stability and accelerate structural reforms. They welcomed the efforts of the Bank of Lithuania to implement Financial Sector Assessment Program recommendations. They emphasized the need for energy and transport privatization, the modernization of the agriculture sector, and streamlining of the legal framework to enhance transparency, governance, and the overall business environment.